EXAMINE THE ROLE OF MOTIVATION IN UTAUT MODEL ON THE USE OF CLOUD COMPUTING BY SMEs DURING COVID-19 PANDEMIC - Marwan Al Fajri; Erwin Setiawan Panjaitan; Hanes Hanes (Sean Institute, 2021)
The 2019 Corona Virus Disease (COVID-19) pandemic is affecting the business sector in Indonesia, especially Small and Medium Enterprise (SMEs) that contribute greatly to the economy which impacted on decrease in revenue due to health protocols. This study aims to examine the role of motivation in the use of cloud computing technology by SMEs during the pandemic by combining it with the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The research method uses quantitative data to test hypotheses that have been formulated through a survey of 129 SMEs in Medan using cloud computing technology since the pandemic. Questionnaires are distributed online and offline containing 25 indicators of variables arranged using the Likert scale. The data processing in this study used equation models from Structural Equation Modeling (SEM) and Smart Partial Least Square (SmartPLS) software. The results of this study received a positive response and showed a significant influence on motivation variable. SME actors have the motivation to survive in the sustainability of their business by using cloud computing technology as a necessity. So that the effect on the intention to use (behavior intention) to use cloud computing technology affects the actual use by SMEs.